Study of Suspended Impurities Origin and Composition in the Treatment Process of Johkasou System - Yenni Trianda; Reni Desmiarti; Tomonari Fujisawa; Yasushi Ishiguro; Fusheng Li (Department of Chemical Engineering, Universitas Gadjah Mada, 2019)
Johkasou system is widely used in Japan for household wastewater treatment and have played important roles in maintaining the water environment. However, out of the total units used in Gifu Prefecture, about 10% cannot meet the quality requirement for the effluent transparency above 30 degrees. Previous studies have shown clearly that the reason is mainly attributed to suspended impurities that remain in the water after treatment, with more than 96% being consisted of fine particles with sizes of 0.5-1.0 μm. A detailed investigation for identifying the origin and composition of the fine particles is necessary in order to find the approaches to improve the treatment function of the related Johkasou units. The analysis by Flow Cytometry suggested that the organic fine particles could be grouped into bacterial fraction, existed in all tanks of the Johkasou, and non-bacterial fraction that was confirmed mainly existed in anaerobic tanks, thus suggesting the lower transparency of Johkasou's effluent was greatly contributed by the bacterial fraction. PCR-DGGE further identified that some of the bacteria contained in the effluent were originated from the anaerobic tank.